Heeding the call of the grassroots: FOR THE PEOPLE: In a democracy, leaders ignore the sentiments on the ground at their own peril - Ariff, Syed Umar (New Straits Times, 2013)
MAN in a worn blue shirt disembarked from a boat, which he moored to a small makeshift wooden jetty in the seaside village of Kampung Minyak Beku, Batu Pahat.